Models of Adaptive Targeted Forecasting of Socio-Economic Region Development Indicators - DAVNIS, Valeriy Vladimirovich; DOBRINA, Maria Valeryevna; CHEKMAREV, Artem Vitalievich; TINYAKOVA, Viktoria Ivanovana (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The aim of the paper is description of the new approach, which provides the construction of models having the opportunity to reflect in the predicted trajectories of the plans, the expected implementation of which in the future period will lead to changes in the past patterns of socio-economic development of the region. In order to implement this idea, it is proposed to use the adaptive mechanism of targeted adjustment of the forecast model coefficients. Correction is based on the newly received observation data. As a newly arrived observation, a specially formed target value is used, in which the plan is concentrated on changing existing patterns. It is possible to conduct multivariate predictive calculations depending on the variation of target settings, followed by an assessment of the obtained options’ preference according to special criteria. Results : computational experiments with models built on real data showed that the proposed approach is a fairly effective tool for developing forecasts of the socio-economic development of regions and municipalities.